Phenotypes and treatment outcomes in idiopathic pulmonary arterial hypertension patients with comorbidities - Skowasch, Dirk; Klose, Hans; Ewert, Ralf; Wilkens, Heinrike; Richter, Manuel; Rosenkranz, Stephan; Setzer, Gesine; Grünig, Ekkehard; Halank, Michael (ERJ Open Research, 2024)
Idiopathic pulmonary arterial hypertension (IPAH) is often diagnosed in elderly patients with many comorbidities. Whereas a clear treatment strategy and risk assessment is recommended for patients with rare classical IPAH, monotherapy with phosphodiesterase type 5 inhibitors or endothelin receptor antagonists followed by regular follow-up and individualised therapy should be used for patients with many cardiopulmonary comorbidities. Here, we focus on these patients with IPAH and comorbidities, present a review of the literature with a focus on recently published work and summarise factors that may help to provide guidance for individualised treatment approaches in such patients.